Methodological Modifications in a Longitudinal Qualitative Research Design. Issue 4 (November 2013) - Koro-Ljungberg, Mirka; Bussing, Regina
This article explores methodological shifts in longitudinal qualitative research and illustrates how researchers can maintain methodological continuity while staying open to necessary modifications. We describe methodological modifications and changes that occurred during our longitudinal research process. These change processes were initiated due to general advances in the field of qualitative research methodology, personal research experiences gained during the research process, and preliminary analysis findings. The change processes complicated our methodological decision making and simultaneously refined study purposes and analytical intentions. The investigation of change over time, time in context, and time and texture also play a significant role in our examples and reflections in this article. We argue that careful analysis and accounting of methodological continuity, modification, and changes can strengthen the trustworthiness of longitudinal studies, an important goal considering the methodological complexity often associated with longitudinal qualitative research.